2018
DOI: 10.1016/j.ctcp.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and embodiment associated with Alexander Technique lessons or with acupuncture sessions: A longitudinal qualitative sub-study within the ATLAS trial

Abstract: Background and purposeA large randomised controlled trial found that the provision of either Alexander Technique lessons or acupuncture, for those with chronic neck pain, resulted in significantly increased self-efficacy when compared with usual care alone. In turn, enhanced self-efficacy was associated with significant reductions in neck pain at 6 and 12 months. In this analysis we explore the perspectives of participants within the trial, with the aim of gaining a better understanding of how these interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Scepticism (24 mentions) is depicted as an undesirable starting-point characteristic which acupuncture treatment can shift—”attitude changes with improvement in their condition” (9.a/114). A reinforcing cycle of improved outcomes with increased buy-in to the system responsible is perceived, and acupuncture’s capacity to potentiate positive change and enhance self-efficacy is acknowledged as it is in current literature [ 47 ]. Respondent 43 (amongst others) is repeatedly concerned with acupuncture’s impact on individuals’ ability to cope , emphasising that this is a more important factor than changes to symptoms, in particular pain levels (see, for e.g., 10.12.c/43 and 10.13.c/43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scepticism (24 mentions) is depicted as an undesirable starting-point characteristic which acupuncture treatment can shift—”attitude changes with improvement in their condition” (9.a/114). A reinforcing cycle of improved outcomes with increased buy-in to the system responsible is perceived, and acupuncture’s capacity to potentiate positive change and enhance self-efficacy is acknowledged as it is in current literature [ 47 ]. Respondent 43 (amongst others) is repeatedly concerned with acupuncture’s impact on individuals’ ability to cope , emphasising that this is a more important factor than changes to symptoms, in particular pain levels (see, for e.g., 10.12.c/43 and 10.13.c/43).…”
Section: Resultsmentioning
confidence: 99%
“…Individual patient diagnosis emerges as a priority with regard to response/non-response, with consensus found across many areas and specifically with regard to depression (see, for example, 11.18.c/4 and 11.18.c/18) that the innate and unique characteristics of each individual patient are the deciding factor with regard to response level. There are repeated pleas for the diagnostic specificity of the medicine (such as Respondent 63’s answers above) and acknowledgement of the non-specific treatment effects known to accompany it [ 47 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different somatic forms are reported to have a wide variety of health and well-being benefits for people living with chronic pain. Physical benefits, for example, include flexibility, balance, muscle tone, reduction of days in pain, increased mobility and reduced perception of pain, especially in musculoskeletal pain ( Little et al, 2008 ; Webb et al, 2013 ; Wenham et al, 2018 ; Paolucci et al, 2019 ; Ahmadi et al, 2020 ). A randomised controlled trial (RCT) of Alexander Technique lessons, exercises and massage for chronic and recurrent back pain found that the effect of 24 lessons in the Alexander Technique after 1 year was a “42% reduction in Roland disability score and an 86% reduction in days in pain compared with the control group” ( Little et al, 2008 , p. 4).…”
Section: Background To Somatic Practices In Chronic Pain Managementmentioning
confidence: 99%
“…Use of the ICJI approach is also appropriate to embed within a qualitative longitudinal design that recruits one or more cohorts of eligible caregivers to conduct repeat interviews at different time points. 39 One or more data collection teams may be needed depending on the sample design, desired turnaround time to collect the data and other logistical considerations. We recommend that each team be composed of two members-an interviewer and a dedicated notetaker, which is customary in qualitative investigations.…”
Section: Sampling Techniques and Data Collectionmentioning
confidence: 99%